Prenatal exposure to organochlorine compounds and lung function during childhood - Abellan, Alicia; Sunyer, Jordi; Garcia-Esteban, Raquel; Basterrechea, Mikel; Duarte-Salles, Talita; Ferrero, Amparo; Garcia-Aymerich, Judith; Gascon, Mireia; Grimalt, Joan O.; Lopez-Espinosa, Maria-Jose; Zabaleta, Carlos; Vrijheid, Martine; et al. (Environment international, 2019)
Prenatal exposure to organochlorine compounds (OCs) can increase the risk of reported respiratory symptoms in children. It remains unclear whether these compounds can also impact on lung function. We assessed the association between prenatal exposure to OCs and lung function during childhood. We included 1308 mother-child pairs enrolled in a prospective cohort study. Prenatal concentrations of p,p′-dichlorodiphenyltrichloroethane [p,p′-DDT], p,p′-dichlorodiphenyldichloroethylene [p,p′-DDE], hexachlorobenzene [HCB], and seven polychlorinated biphenyls [PCBs] were measured in cord blood. Spirometry was performed in the offspring at ages 4 (n = 636) and 7 years (n = 1192). More than 80% of samples presented quantifiable levels of p,p′-DDE, HCB, PCB-138, PCB-153, and PCB-180; p,p′-DDE was the compound with the highest median concentrations. At 4 years, prenatal p,p′-DDE exposure was associated with a decrease in forced expiratory volume in 1 s (FEV1) in all quartiles of exposure (e.g., third quartile [0.23–0.34 ng/mL]: β for FEV1 −53.61 mL, 95% CI −89.87, −17.35, vs. the lowest). Prenatal p,p′-DDE levels also decreased forced vital capacity (FVC) and FEV1/FVC, but associations did not reach statistical significance in most exposure quartiles. At 7 years, p,p′-DDE was associated with a decrease in FVC and FEV1 in only the second quartile of exposure (e.g. β for FEV1 −36.96 mL, 95% CI −66.22, −7.70, vs. the lowest). Prenatal exposure to HCB was associated with decreased FVC and FEV1, but in only the second quartile and at 7 years (e.g. [0.07–0.14 ng/mL]: β for FEV1 −25.79 mL, 95% CI −55.98, 4.39, vs. the lowest). PCBs were not consistently associated with lung function. Prenatal exposure to p,p′-DDE may decrease lung function during childhood, especially FEV1 and at medium levels of exposure. Further and deeper knowledge on the impact of environmental chemicals during pregnancy on lung development is needed. •Current low but widespread human exposure to banned organochlorine compounds•Prenatal exposure to organochlorine pesticides linked to lower lung function in childhood•Low levels found in current populations can be harmful for offspring respiratory health.